Effects of political dispensations on the pattern of urban expansion in the Osogbo metropolis, Osun State, Nigeria (2014)
Most studies on urban growth have focused on measuring the extent and rate of urban growth, while some focused on the understanding of factors that initiate and sustain city growth at local and global scales. Only anecdotal studies exist on the effects of different political regimes on urban growth. Both military and democratic governments enacted and implemented various urban and related policies that might have impacted the urban expansion. This is because a regime’s ideology (be it civilian or military) could be a crucial growth-determining factor. This study compares urban growth in Osogbo, Nigeria, during military and civilian regimes, using eight landscape metrics. Landsat images of the Osogbo metropolis for the years 1986, 1991, 1996, 1999, 2003, 2010 and 2014 were selected, based on the progression of political regimes in Nigeria. Where necessary, the images were gap-filed and co-registered to a common datum. Supervised classification was used in identifying built-up areas over-time, while change vector analysis was used in exploring growth pattern between the civilian and the military regimes. Landscape metrics were used to assess the process and impacts of urban expansion, while analysis of variance was used to assess variations in growth between the two dispensations. There has been considerable growth in Osogbo metropolis since its creation in 1991, and significant differences exist in urban growth rates between military and civilian regimes (F=7.920, P<0.05). However, the effect of urban growth on distance to central business district, available open space, urban sprawl, and shape of built-up areas, are not significantly different between the military and the civilian regimes. Urban expansion occurred primarily through expansion of existing urban areas rather than spontaneous and detached development. Therefore, one of the most difficult conclusions from this study is that urban benefits derived through city growth do not necessarily have anything to do with the type of city administrations in place.